2023
DOI: 10.3390/jcm12144610
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Concentration of Adipocyte Fatty Acid-Binding Protein Correlates with the Markers of Abdominal Obesity Independently of Thyroid Hormones in Non-Obese Women with Polycystic Ovary Syndrome

Abstract: Adipocyte fatty acid-binding protein (A-FABP) is mainly expressed in adipocytes. The risk of abdominal obesity and autoimmune thyroid disease is increased in women with polycystic ovary syndrome (PCOS). The objective of this study was to explore the relationship of serum concentration of A-FABP with parameters of obesity, e.g., waist to hip ratio (WHR) and the amount of adipose tissue assessed by bioelectrical impedance analysis (BIA), and thyroid hormone homeostasis in women with PCOS. We examined 66 women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…In the current study, we observed a slight increase in TSH and T4, which is positively correlated with the high FABP4 levels [26]. Polak et al recently reported, in a study of 66 females with polycystic ovary syndrome (PCOS) and 67 healthy controls, that serum concentrations of FABP4 were significantly higher in the PCOS group compared to the control group [27]. Another study, including an equal number of subclinical hypothyroid, overt hypothyroid, and healthy patients (n = 40 in each group), found that in patients with subclinical and overt hypothyroidism, the level of FABP4 was high, and the elevation closely correlated with high TSH [28].…”
Section: Discussionsupporting
confidence: 69%
“…In the current study, we observed a slight increase in TSH and T4, which is positively correlated with the high FABP4 levels [26]. Polak et al recently reported, in a study of 66 females with polycystic ovary syndrome (PCOS) and 67 healthy controls, that serum concentrations of FABP4 were significantly higher in the PCOS group compared to the control group [27]. Another study, including an equal number of subclinical hypothyroid, overt hypothyroid, and healthy patients (n = 40 in each group), found that in patients with subclinical and overt hypothyroidism, the level of FABP4 was high, and the elevation closely correlated with high TSH [28].…”
Section: Discussionsupporting
confidence: 69%